Hearing Screening Of Infants In Neonatal Unit, Hospital Universiti Sains Malaysia Using Transient Evoked Otoacoustic Emissions - Md. Daud, Mohd Khairi (2001)
Objective: this prospective study reports on the prevalence of hearing impairment in neonatal unit population (NICU graduates and less severe ill infants). Design: from 15th February, 2000 to 15th March, 2000 and 15th February, 2001 to 15th May, 2001, 401 neonates were screened with transient evoked otoacoustic emissions (TEOAE) followed by second stage screening of the infants who had failed the initial test. Results: 370 (92.27°.4,) infants passed the primary screen for both ears. Eight (2%) infants failed one ear and twenty three (5.74%) infants failed both ear, adding up to 7.740/0 planned for second stage screening. Five out of twenty two infants who had come for the follow up failed the screening resulting the prevalence of hearing impairment of 1.28%. Craniofacial malformations, very low birth weight, ototoxic medication, stigmata I syndromes associated with hearing loss and hyperbilirubinaemia at the level of exchange tranfusion were identified to be independent significant risk factors for hearing impairment. The mean total test time was 5.43 minutes. Poor apgar score and mechanical ventilation of more than 5 days were not found to be associated with hearing impairment in the present study population. Conclusion: Hearing screening in high-risk neonates revealed a total of 1.28%, with hearing loss. Significant risk factors were craniofacial malformations, very low birth weight, ototoxic medication, stigmata I syndromes associated with hearing loss and hyperbilirubinaemia at the level of exchange tranfusion. Other perinatal complications did not significantly influence screening results indicating improved perinatal handling in a neonatal population at risk for hearing disorders